(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Weeds and invasive plants cause substantial losses to crop yields and quality, which directly affect food security and safety. According to reports approximately one-third yield losses occur globally due to weeds, in which contribution of invasive noxious weeds is enormous. The eradication of these plants is a big challenge for developing countries like India. It is a need of present time to enumerate the invasive plants and weeds of popular crops, so that concrete steps may be taken to eradicate these harmful plants. Considering above, a preliminary survey of invasive plant species and weeds of Shamli district of Uttar Pradesh was conducted and was found a total richness of 161 species belonging to 108 genera and 39 families. Most of these alien species (57.14 ) were introduced from tropical America including South and North America, followed by tropical Africa and other parts of Africa (17.39). Maximum number of species were reported from the family Asteraceae (31), followed by Papilionaceae (13) Amaranthaceae (12), Solanaceae and Poaceae with 10 species each. The data revealed that invasive plant species and weeds are becoming threat to the native flora and crops as they colonize rapidly and replace native species.